A proposed model on the impact of internal control quality on accounting information system effectiveness in Nigeria / Shamsudeen Ladan Shagari, Akilah Abdullah and Rafeah Mat Saat - Shagari, Shamsudeen Ladan; Abdullah, Akilah; Mat Saat, Rafeah (Penerbit UiTM (UiTM Press), 2018)
The overwhelmingly rapid adoption of e-business technology in the Nigerian banking sector has resulted in new challenges particularly in the area of internal control. Although there are conflicting findings on the use of Accounting Information System and internal problems in the banking sector, the fact remains that internal control is associated with fraud. In this regards, for banks to effectively detect and prevent fraud, the use of Accounting Information System as tool for effective internal control is necessary. This study aims to propose a model of the effect of internal control quality in Nigerian banking sector. it is hypothesised that administrative control, data control, and output control has significant influence on internal control quality. The study further hypothesised that internal control quality would significantly influence AIS effectiveness uses organisation as unit of analysis with commercial banks that are listed on the Nigerian Stock Exchange as the target population. A quantitative data will be gathered using cross-sectional survey approach. Ordinary least square will be used for data analysis. The findings of this study will provide a solution to bank managers and other stakeholders in the banking sector regarding internal control weakness experiences over the years.